Guidance in computer-supported collaborative inquiry learning: Capturing aspects of affect and teacher support in science classrooms - Pietarinen Tarja; Palonen Tuire; Vauras Marja (SPRINGER, 2022)
Technology-enhanced collaborative inquiry learning has gained a firm position in curricula across disciplines and educational settings and has become particularly pervasive in science classrooms. However, understanding of the teacher’s role in this context is limited. This study addresses the real-time shifts in focus and distribution of teachers’ guidance and support of different student groups during in-person computer-supported collaborative inquiry learning in science classrooms. Teachers’ self-perceptions of their guidance and affect were supplemented with students’ self-reported affect. A mixed-methods approach using video analyses and questionnaire data revealed differences between teacher guidance and support associated with teacher perceptions and group outcomes. Groups’ prior science competence was not found to have an effect on teacher guidance and support, rather the teachers guided the groups they perceived as motivated and willing to collaborate. Teacher affect was compounded by student affect, suggesting that consideration of the reciprocal perceptions of teachers and students is necessary in order to understand the teachers’ role in collaborative learning.